Effects of sub-atmospheric pressure on keyhole dynamics and porosity in products fabricated by selective laser melting - Tan, Pengfei (2021)
A powder-scale multi-physics model is developed to investigate the keyhole dynamics and porosity in products fabricated by selective laser melting (SLM) under the sub-atmospheric pressure. The effects of the sub-atmospheric pressure on the plume attenuation of the laser beam, vaporization temperature and vapor recoil pressure are taken into account. The thermo-fluid behaviour in the melt pool under the atmospheric and sub-atmospheric ambient pressure is analysed in the SLM process. The simulation results suggest that the reduction of the sub-atmospheric pressure can increase the melt pool depth, whereas the effects are insignificant under the low sub-atmospheric pressure. As compared with the atmospheric pressure, the sub-atmospheric pressure leads to the decrease of the average temperature and the increase of the average recoil pressure on the keyhole surface, which is in favour of increasing keyhole stability and maintaining keyholes open. Consequently, the sub-atmospheric pressure can help to improve the keyhole stability and thus minimize pore defects in SLM-built products.